Analysis of the Effect of Sinker on Bearing Capacity of Anchor in Calm Buoy Mooring System: Case Study of SBM Pengapon Semarang - Murdjito, Murdjito; Djatmiko, Eko Budi; Melani, Agnes Teresa (Pusat Publikasi Ilmiah Institut Teknologi Sepuluh Nopember, 2024)
The addition of sinkers on the mooring line is generally used to support the anchor in maintaining its position in extreme environmental conditions. In this study, the author will analyze the effect of sinkers on the mooring line tension and the bearing capacity of the anchor. The sinker variations in this analysis are 10, 15, and 20 tons, which will be added to the asymmetric mooring line of CALM Buoy SPM Pengapon Semarang. The type of anchor SPM is Stevpris MK III on soft clay soil type. The author first analyses the line tension in each environmental loading condition and then analyses the anchor's bearing capacity. The analysis results show that the largest tension occurs in line 3 without a sinker in DEC conditions with an environmental load direction of 314.24 deg, 1301.19 kN (End A) and 1310.43 kN (End B). In the analysis of the holding capacity of the anchor, the author refers to the SOF ABS Class 2019 and the charts of Appendix D2 and D6 API RP 2SK. The results indicate that the gradation of weight and position of the sinker causes the line tension between the sinker and the fairlead to increase linearly, with an average percentage increase of 1.35%. Meanwhile, the bearing capacity of the anchor, which includes required holding capacity, anchor weight, and estimated drag distance/fluke length, decreased with an average percentage of 7.46%, 15.39%, and 4.79%. Based on the consideration of the End A tension analysis results in the DEC condition, it is stated that the 20-ton sinker in position 1 is a suitable variation of the sinker in this SPM Pengapon Semarang case study.